Pembuatan Pembangkit Listrik Tenaga Hybrid Solar Cell dan Pico Hydro di Dusun Wukirsari - Slamet Hani; Gatot Santoso; Muhamad Wahyu Firmansyah (Journal of Appropriate Technology for Community Services, 2021)
The source of water flow in rivers or irrigation canals has a relatively small flow rate of water, which can be used as a pico hydropower plant. One of the main components of a pico hydropower plant is a water wheel, a hybrid pico hydropowerplant is a combination of hydroelectric power and solar power. By utilizing the power of the water flow in a small river or ditch in Wukirsari hamlet, we designed a waterwheel that will convert the energy of motion into electrical energy. The solar panel system designer uses a 50 wp solar cell, a 300 W inverter, a 10 Ampere solar charger controller, and a 12 Volt, 32 Ah battery. The no-load test results on the performance of the single pinwheels and the performance of the double pinwheels at a water level of 37 cm get an average power of 3.2 W and 2.11 W. The resulting voltage is 6.72 V, the current is 0.46 A for a single mill, while for the double pinwheel the voltage is 5,26 , and the current is 0.38 A. From the experimental results, it is better if the single pinwheel and the double pinwheel are used. In a series of no-load solar panels fromPower test results, at 11.00 GMT+7 the highest power value was 33.25 W. The electricity generated by the pico hydro hybrid was used by the people of Wukirsari Hamlet as street lighting. Key words: water wheel, hybrid power, solar panels